Conductive particle dispersion liquid, method for producing the same, coating liquid for forming conductive film, and substrate with conductive film

CN116829254BActive Publication Date: 2026-10-20JGC CATALYSTS & CHEMICALS LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280014219.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-30
Publication Date
2026-10-20
Estimated Expiration
2042-03-30

AI Technical Summary

Benefits of technology

[0004]发明要解决的技术问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385164070000031
    Figure BDA0004385164070000031
  • Figure BDA0004385164070000111
    Figure BDA0004385164070000111
  • Figure BDA0004385164070000121
    Figure BDA0004385164070000121
Patent Text Reader

Abstract

The present invention relates to a dispersion liquid of conductive particles containing antimony-doped tin oxide. The conductive particles contain clusters of chain-like particles formed by linking primary particles, the dispersion liquid contains 1 to 20 mass% of the conductive particles, and, relative to the content of the conductive particles, 0.05 to 0.5% by mass of a cluster-forming agent. In the particle size distribution of the dispersion liquid measured with a dynamic light scattering particle size distribution meter, the volume average particle size is 10 to 50 nm; the difference (D 16 D 84 ) between the particle size D 84 at 84% of the cumulative volume and the particle size D 16 at 16% of the cumulative volume is 3 to 50 nm. According to such conductive particles, low resistance of a conductive film can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dispersion containing conductive chain particles, a coating liquid for forming a conductive film prepared using the dispersion, and a substrate with a conductive coating. Background Technology

[0002] Conventionally, conductive films are formed on substrates using coating solutions containing conductive particles. Transparent conductive films are used in display devices, touch panels, solar cells, etc. To balance the transparency and low resistance of the conductive film, coating solutions containing chain-like conductive particles are used. For example, in Japanese Patent Application Publication No. 2019-157026 (Patent Document 1), it is known that a coating solution containing alkoxysilane oligomers that readily bind to chain-like conductive particles is used as an adhesive component to improve the strength of the film.

[0003] Furthermore, in Japanese Patent Application Publication No. 2006-339113 (Patent Document 2), it is known to use chain-like particles to obtain a film with excellent antistatic and electromagnetic wave shielding properties. In Patent Document 2, chain-like particles are manufactured by adjusting the pH to arrange the primary particles into a chain after ion exchange treatment of a dispersion of conductive primary particles, and by adding an alcohol to hydrolyze an organosilicon compound to link the primary particles. Summary of the Invention

[0004] The technical problem that the invention aims to solve

[0005] In the coating liquid of Patent Document 1, the insulating adhesive component gradually covers the surface of the chain-like conductive particles. During film formation, the structure of the insulating component exists between the chain-like conductive particles, making it difficult to form multiple conductive paths. That is, there is a technical problem that the conductivity decreases over time, and it is impossible to obtain the same conductivity as the film formed from the initial coating liquid.

[0006] Furthermore, in recent years, there has been a demand for low resistance in conductive films. However, the chain-like conductive particles disclosed in Patent Documents 1 and 2 cannot simultaneously achieve both low resistance and high hardness.

[0007] Therefore, the object of the present invention is to provide conductive particles that can achieve low resistance in conductive films.

[0008] Technical means to solve technical problems

[0009] This invention relates to a dispersion of conductive particles containing antimony-doped tin oxide (ATO). The conductive particles comprise clusters of chain-like particles formed by the linkage of primary particles. The dispersion contains 1% to 20% by mass of conductive particles and 0.05% to 0.5% by mass of a cluster-forming agent relative to the content of conductive particles. In the particle size distribution of this dispersion measured using a dynamic light scattering particle size analyzer, the volume average particle size is 10 nm to 50 nm; the particle size D accumulated from the smallest particle size side to 16% is measured by volume. 16 Particle size D when accumulated to 84% 84 The difference (D) 84 -D 16 The wavelength range is 3nm to 50nm. Cluster-forming agents are added to cluster the chain-like particles. Acids or polymeric agglomerants are used as cluster-forming agents.

[0010] Furthermore, the method for manufacturing the conductive particle dispersion of the present invention includes: a step of preparing a dispersion of chain-like particles formed by connecting primary particles, wherein the primary particles contain ATO; and a step of adding 0.05% to 0.5% by mass of a dispersant relative to the sum of the mass of the primary particles present in the dispersion and the mass of the chain-like particles present in the dispersion. Detailed Implementation

[0011] This invention relates to a dispersion of conductive particles containing ATO, wherein the conductive particles comprise clusters of chain-like particles formed by the linkage of primary particles. The dispersion contains 1% to 20% by mass of conductive particles and, relative to the content of conductive particles, 0.05% to 0.5% by mass of a cluster-forming agent. When the particle size distribution of this dispersion was measured using a dynamic light scattering particle size analyzer, the volume average particle size was 10 nm to 50 nm; the particle size D accumulated from the smallest particle size side to 16% was measured on a volume basis. 16 Particle size D when accumulated to 84% 84 The difference (D) 84 -D 16 The particle size range is 3nm to 50nm. Furthermore, this particle size difference (D) is then... 84 -D 16 This is called the width of the particle size distribution. In this case, the average particle size of the primary particles is preferably 3 nm to 10 nm.

[0012] If the conductive particles exceed 20% by mass, it becomes difficult to form clusters of an appropriate size, and it is also difficult for them to exist stably at that size. When the amount is less than 1% by mass, the amount of conductive particles is too small to be practical. Furthermore, in order for clusters to form, the cluster forming agent needs to be at least 0.05% by mass of the conductive particles; if it exceeds 0.5%, conductivity may be significantly reduced.

[0013] The presence of clusters formed by chain-like particles can be determined from the particle size distribution measured by a dynamic light scattering method. That is, if a large number of clusters are present, the volume-average particle size increases, and the particle size distribution also widens. If the volume-average particle size and the width of the particle size distribution are within the aforementioned ranges, the effects resulting from the presence of clusters can be obtained. For example, low resistance can be achieved due to the good formation of conductive paths. In coating solutions using this dispersion, the area of ​​contact (reaction) between conductive particles and other components (binders, etc.) is smaller, thus suppressing changes over time. Since the film obtained through this coating solution controls the size of the clusters, light scattering (haze) can be suppressed without compromising optical properties.

[0014] Furthermore, the cluster structure is fixed by adding 3% to 25% by mass of alkoxysilane relative to the content of conductive particles. Therefore, even with stirring and ultrasonic treatment (ultrasonic imprinting) of the dispersion, the clusters are difficult to redisperse. If the amount of alkoxysilane is too small, the clusters may not be immobilized. Conversely, if too much is added, the alkoxysilane may excessively cover the cluster surface, potentially reducing conductivity. The preferred amount of alkoxysilane added is 3% to 15%. Alkoxysilane is typically referred to as "R". 1 n-Si(OR 2 ) 4-n [Equation 1]” is used in this paper. R is used in this paper. 1 and R 2 It consists of hydrogen atoms, halogen atoms, and unsubstituted or substituted hydrocarbon groups having 1 to 10 carbon atoms, which may be the same as or different from each other. Furthermore, n is an integer from 0 to 3. Specific examples of alkoxysilanes are shown in Table 1.

[0015] [Table 1]

[0016]

[0017] Furthermore, the chain-like particles are particles composed of three or more primary particles containing ATO linked in a chain. The particles may have branched connections. That is, the main chain may consist of three or more primary particles linked together, but branched connections are also possible. The primary particles are monodisperse inorganic particles. The average particle size of the primary particles is preferably 3 nm to 10 nm. The particle size of any 100 primary particles is measured from images taken by transmission electron microscopy (TEM), and the average value is taken as the average particle size. Furthermore, 50 arbitrary particles are selected from this image, and the number of connections for each particle is measured. The average number of connections for the 50 particles is the average number of connections. The average number of connections is preferably 3 or more, and particularly preferably 5 or more. If the average number of connections for the primary particles is low, the improvement in conductivity may not be sufficiently obtained. If the average particle size is too small, the crystallinity is low, and the conductivity of the primary particles themselves may not be sufficiently obtained. Conversely, if the average particle size is too large, it is difficult to develop a chain-like structure, and even if chain-like formation occurs, conductive pathways are difficult to form effectively, and the conductivity of the film may not be sufficiently obtained. In primary particles, elements other than antimony and tin oxide may be included if they do not significantly impede conductivity.

[0018] Next, the method for manufacturing the dispersion of conductive particles will be described. First, a dispersion of chain-like particles formed by the linkage of primary particles containing ATO is prepared. The dispersion of chain-like particles can be prepared using known methods such as those disclosed in Japanese Patent Application Publication No. 2006-339113. A cluster-forming agent, comprising 0.05% to 0.5% by mass of the conductive particle component (the total amount of conductive particles present as primary particles and conductive particles present as chain-like particles in the dispersion), is added to this dispersion. This forms clusters of chain-like particles. The structure of the clusters can be controlled by adjusting the concentration of the chain-like particles in the dispersion, pH, temperature, and stirring time. Using the cluster-forming agent, the chain-like particles form three-dimensional clusters through two-dimensional and three-dimensional linkage. Acids and polymeric coagulants can be used as cluster-forming agents. Examples of polymeric coagulants include nonionic, anionic, cationic, amphoteric, polyamine, and dicyandiamide coagulants. The appropriate amount added varies depending on the type of cluster-forming agent. Examples of acids include organic acids such as formic acid, acetic acid, citric acid, and benzoic acid; and inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, hydroiodic acid, and tetrafluoroboric acid. Hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid are preferred as they are readily soluble in water and industrially available.

[0019] <Coating Liquid>

[0020] A coating solution is prepared by adding a binder component and a solvent to a dispersion of such conductive particles. Specifically, the coating solution of the present invention comprises conductive particles containing ATO, an alkoxysilane oligomer (binder component), and a solvent. The conductive particles comprise clusters of chain-like particles formed by the linkage of primary particles. The coating solution contains 0.05% to 0.5% by mass of a cluster-forming agent and 25% to 300% by mass of the alkoxysilane oligomer, which are the same as the conductive particles. In the particle size distribution of this coating solution measured using a dynamic light scattering particle size analyzer, the volume average particle size is 70 nm to 600 nm; the particle size D accumulated from the smallest particle size side to 16% is measured by volume. 16 Particle size D when accumulated to 84% 84 The difference (D) 84 -D 16 The particle size ranges from 60 nm to 800 nm. When binder components and solvents are added to the dispersion of conductive particles, the clusters solidify more slowly, forming large structures (flocs). Therefore, in measurements using dynamic light scattering methods, the volume average particle size and the width of the particle size distribution are larger compared to the aforementioned dispersion.

[0021] After coating, the solvents used herein can be removed through a drying process or similar steps. Hydrophilic organic solvents such as alcohols, glycols, glycol ethers, and ketones that do not impede cluster structure control are suitable. Specifically, examples include 1-methoxy-2-propanol, diacetone alcohol, ethylene glycol, diethylene glycol, methanol, ethanol, isopropanol, and acetone.

[0022] The weight-average molecular weight of the alkoxysilane oligomer is preferably between 1000 and 20000. The alkoxysilane oligomer is a hydrolyzed polymer of the alkoxysilane represented by Formula 1 above, where n is an integer from 0 to 2. When n is 3, oligomers cannot be formed because they can only bond between two molecules. Smaller n is preferred, and alkoxysilanes with n of 0 are most preferred. Using such alkoxysilanes reduces the amount of organic components that are difficult to conduct electricity between clusters, resulting in high conductivity.

[0023] Furthermore, as mentioned above, the coating solution contains 25% to 300% alkoxysilane oligomers at the level of conductive particles. That is, the mass ratio of conductive particles to alkoxysilane oligomers is in the range of 80:20 to 25:75. If there is too little alkoxysilane oligomer, the binder component will be insufficient, potentially resulting in inadequate film hardness. Conversely, if there is too much, excessive reaction with the surface of the cluster-forming particles occurs in the coating solution, potentially reducing the storage stability of the coating solution.

[0024] The embodiments of the present invention will be described in detail below.

[0025] Example

[0026] [Example 1]

[0027] First, an aqueous dispersion containing ATO particles (primary particles) was prepared (ATO particle average size 5 nm, solids concentration 20.0% by mass, pH 6.9). A zwitterionic exchange resin, equivalent to 40% by mass of the ATO particle solids, was added to this dispersion and stirred at 25°C for 2 hours. Afterward, the zwitterionic exchange resin was separated using a metal mesh. This resulted in ATO particles linked in a chain, yielding an aqueous dispersion of chain-like particles.

[0028] The solid component concentration of the aqueous dispersion of the chain particles was diluted to 5% by mass with pure water. 0.5g of hydrochloric acid (1.0% by mass) was added to 100.0g of this aqueous dispersion as a cluster forming agent, and the mixture was stirred at 25°C for 5 minutes. Thus, the chain particles formed clusters, yielding a dispersion of the conductive particles of the present invention.

[0029] <Coating Liquid>

[0030] A coating solution was prepared by adding a binder component and a solvent to the dispersion of the conductive particles. In this embodiment, 60.3 g of the conductive particle dispersion was stirred at 25°C while 2.7 g of pure water was added. Next, 17.0 g of Solmix AP-11 (an alcohol mixture with ethanol as the main solvent) was added. After stirring for 5 minutes, 20.0 g of the binder component was added while stirring. The coating solution was obtained by filtration after stirring at 25°C for 15 minutes. Here, as the binder component, an ethanol dispersion of an alkoxysilane oligomer with a molecular weight of 4980 (solids concentration 9.9 by mass) obtained by hydrolyzing tetramethoxysilane was used.

[0031] <Film-coated substrate>

[0032] The coating solution was applied to a glass substrate using a rod coating method and dried at 80°C for 1 minute. Further, it was heated in a dryer at 130°C for 30 minutes. This yielded a film-coated substrate.

[0033] Tables 2 and 3 show the preparation conditions of the dispersion and coating solutions of the conductive particles. Furthermore, the results of the following physical property measurements are also shown in the same tables. Additionally, the examples and comparative examples described later were performed in the same manner.

[0034] (1) Determination of the concentration and quantity of conductive particles

[0035] The dispersion was weighed into a magnetic crucible and heated at 1000℃ for a certain time. Based on the weight ratio before and after heating, the concentration of the solid component of the conductive particles was determined.

[0036] When the dispersion of conductive particles contains solid components other than ATO, an inductively coupled plasma atomic emission spectrometry (ICP-AES) device can be used to measure the dispersion to determine the amount of each element present in the dispersion, thereby determining the amount of conductive particles.

[0037] (2) Content of clustering agent in dispersion

[0038] The dispersion was centrifuged to separate the conductive particles from the supernatant. The elements and their concentrations in the supernatant were determined using an ICP emission spectrometer. This result was compared with a reference obtained from a prior analysis of the clustering agent in the same manner to determine the clustering agent and its concentration in the supernatant.

[0039] (3) Volume average particle size and particle size distribution width

[0040] The dispersion was measured using a dynamic light scattering particle size analyzer (NANOTRAC Wave 2-UT151, manufactured by MICROTRAC) to determine the average particle size and the width of the particle size distribution (particle size difference: D). 84 -D 16 ).

[0041] (4) Pencil hardness

[0042] Using pencils specified in JIS S-6006, the pencil hardness of the film-coated substrate was measured using a surface hardness tester (Traybogia, manufactured by Shin-To Science Co., Ltd.). According to the tester's operating manual, pencils of various hardnesses were used to scan the surface under a 500g load. Scan marks were examined, and the highest hardness value without observed scratches was taken as the pencil hardness value.

[0043] (5) Surface resistivity and storage stability

[0044] The surface resistivity of the film-coated substrate prepared using the freshly prepared coating solution was measured using a surface resistivity meter (High Resistor UX MCP-HT800, manufactured by Mitsubishi Chemical Analite Co., Ltd.). Next, the coating solution was left to stand in a bath at 40°C for 24 hours. Using the heated coating solution, film-coated substrates were prepared in the same manner, and the surface resistivity was measured. Storage stability was evaluated based on the rate of change of surface resistivity (surface resistivity of the film-coated substrate obtained with the heated coating solution / surface resistivity of the film-coated substrate obtained with the initial coating solution).

[0045] The following description records the differences from Example 1.

[0046] [Example 2]

[0047] In this embodiment, polyaluminum chloride (manufactured by Tamaki Chemical Co., Ltd., high-alkalinity aluminum chloride PAC#1000) was used as the cluster forming agent. The concentration was diluted to 0.2% by mass with pure water, and 5.0 g of the diluted solution was added.

[0048] <Coating Liquid>

[0049] No pure water was added to the 63.0 g dispersion of conductive particles, and the mixture was stirred at 25°C.

[0050] [Example 3]

[0051] In this embodiment, polyethyleneimine (manufactured by Fuji Film and Koko Pure Chemicals Co., Ltd., average molecular weight 600) was used as the clustering agent. The concentration was diluted to 2.0% with pure water, and 0.8g of the diluted solution was added.

[0052] <Coating Liquid>

[0053] Add 2.6g of pure water to 60.5g of the dispersion of conductive particles.

[0054] [Example 4]

[0055] In this embodiment, the aqueous dispersion of the chain particles was diluted with pure water to achieve a solids concentration of 10.0% by mass. Further, 1.0 g of hydrochloric acid (1.0% by mass) was added, and the mixture was stirred at 25°C for 5 minutes. Further, tetramethoxysilane was added to immobilize the cluster structure. Here, 4.9 g of the alkoxysilane oligomer used as a binder component in Example 1 was added, and the mixture was stirred at 25°C for 1 hour. Otherwise, the dispersion of conductive particles was prepared in the same manner as in Example 1.

[0056] <Coating Liquid>

[0057] In addition, the dispersion is 32.3g, the amount of pure water added is 30.7g, the amount of solvent (AP-11) added is 18.6g, and the amount of binder component is 18.4g.

[0058] [Example 5]

[0059] In this embodiment, the amount of alkoxysilane oligomer added to immobilize the cluster structure was 24.5 g. Otherwise, the dispersion of conductive particles was prepared in the same manner as in Example 4.

[0060] <Coating Liquid>

[0061] In addition, the dispersion is 38.0g, the amount of pure water added is 25.0g, the amount of solvent (AP-11) added is 24.5g, and the amount of binder component added is 12.5g.

[0062] [Example 6]

[0063] In this embodiment, the aqueous dispersion of chain particles was diluted with pure water to make the solid component concentration 20.0% by mass. In 100.0g of the dispersion, 1.0g of hydrochloric acid (concentration 1.0% by mass) was added as a cluster forming agent.

[0064] <Coating Liquid>

[0065] The dispersion of conductive particles was 15.2g, and the amount of pure water added was 47.9g.

[0066] [Example 7]

[0067] In this embodiment, the aqueous dispersion of chain particles was diluted with pure water to make the solid component concentration 15.0% by mass. In 100.0g of the dispersion, 1.5g of hydrochloric acid (concentration 1.0% by mass) was added as a cluster forming agent.

[0068] <Coating Liquid>

[0069] The dispersion of conductive particles was 20.3g, and the amount of pure water added was 42.7g.

[0070] [Example 8]

[0071] In this embodiment, the aqueous dispersion of chain particles was diluted with pure water to make the solid component concentration 10.0% by mass. In 100.0g of the dispersion, 1.0g of hydrochloric acid (concentration 1.0% by mass) was added as a cluster forming agent.

[0072] <Coating Liquid>

[0073] The dispersion of conductive particles was 30.3g, and the amount of pure water added was 32.7g.

[0074] [Example 9]

[0075] In this embodiment, the aqueous dispersion of chain particles was diluted with pure water to make the solid component concentration 10.0% by mass. In 100.0g of the dispersion, 1.0g of phosphoric acid (concentration 1.0% by mass) was added as a cluster forming agent.

[0076] <Coating Liquid>

[0077] The dispersion of conductive particles was 30.3g, and the amount of pure water added was 32.7g.

[0078] [Example 10]

[0079] In this embodiment, the aqueous dispersion of chain particles was diluted with pure water to make the solid component concentration 10.0% by mass. In 100.0g of the dispersion, 1.0g of nitric acid (concentration 1.0% by mass) was added as a cluster forming agent.

[0080] <Coating Liquid>

[0081] The dispersion of conductive particles was 30.3g, and the amount of pure water added was 32.7g.

[0082] [Comparative Example 1]

[0083] In this comparative example, no chain-like particles were prepared; instead, a cluster-forming agent was directly added to the ATO particles (primary particles). Specifically, in 100.0 g of an aqueous dispersion of the same ATO particles as in Example 1 (solid content concentration 20.0% by mass), 5.0 g of hydrochloric acid (concentration 1.0% by mass) was added as a cluster-forming agent, causing the dispersion to thicken and become gel-like. Therefore, a dispersion and coating solution of conductive particles could not be obtained.

[0084] [Comparative Example 2]

[0085] In this comparative example, an aqueous dispersion of chain-like particles was prepared in the same manner as in Example 1, but without the use of a clustering agent. The aqueous dispersion of the chain-like particles was 15.0 g, and 48.0 g of pure water was added to prepare the coating solution.

[0086] [Comparative Example 3]

[0087] In this comparative example, 3.0 g of hydrochloric acid (1.0% by mass) was added as a clustering agent. The coating solution was prepared in the same manner as in Example 1, except that the dispersion of conductive particles was 61.5 g and the amount of pure water added was 1.5 g. However, agglomeration occurred, and it could not be used as a coating.

[0088] [Comparative Example 4]

[0089] In this comparative example, the same polyaluminum chloride as in Example 2, which served as a clustering agent, was diluted with pure water, and 1.0 g of the diluted solution with a concentration of 5.0% was added.

[0090] Except for the amount of conductive particle dispersion (60.6g) and pure water (2.4g), the coating solution was prepared in the same manner as in Example 1, but agglomeration occurred, and it could not be used as a coating.

[0091] [Comparative Example 5]

[0092] In this comparative example, the same polyethyleneimine as in Example 3, which was used as a clustering agent, was diluted with pure water, and 1.0 g of the diluted solution with a concentration of 5.0% was added.

[0093] Except for the amount of conductive particle dispersion (60.6g) and pure water (2.4g), the coating solution was prepared in the same manner as in Example 1, but agglomeration occurred, and it could not be used as a coating.

[0094]

[0095]

Claims

1. A dispersion, wherein the dispersion contains conductive particles of antimony-doped tin oxide. The conductive particles comprise clusters of chain-like particles formed by the connection of primary particles. The dispersion contains 1% to 20% by mass of the conductive particles, and, relative to the content of the conductive particles, contains 0.05% to 0.5% by mass of a clustering agent. In the particle size distribution of the dispersion measured using a dynamic light scattering particle size analyzer, the volume average particle size is 10 nm to 50 nm; based on volume, the particle size D is the particle size accumulated to 16% from the smaller particle size side. 16 Particle size D when accumulated to 84% 84 The difference (D) 84 -D 16 The wavelength range is 3nm to 50nm.

2. The dispersion as described in claim 1, wherein the clustering agent is an acid or a polymeric coagulant.

3. The dispersion as described in claim 1 or 2, characterized in that, The dispersion contains 3% to 15% by mass of alkoxysilane relative to the content of the conductive particles.

4. A method for manufacturing a dispersion of conductive particles, characterized in that, The manufacturing method includes: The process of preparing a dispersion of chain-like particles connected by primary particles, wherein the primary particles contain antimony-doped tin oxide. Relative to the sum of the mass of particles existing in the primary particle state and the mass of particles existing in the chain particle state in the dispersion, 0.05% to 0.5% by mass of a clustering agent is added, such that the volume average particle size is 10 nm to 50 nm in the particle size distribution measured by a dynamic light scattering particle size analyzer, and the particle size D accumulated from the smallest particle size side to 16% is calculated based on volume. 16 Particle size D when accumulated to 84% 84 The difference (D) 84 -D 16 The process involves 3nm to 50nm.

5. A coating solution, said coating solution being a coating solution for forming a conductive film comprising conductive particles containing antimony-doped tin oxide, an alkoxysilane oligomer, and a solvent. The conductive particles comprise clusters of chain-like particles formed by the connection of primary particles. The coating liquid contains 1% to 20% by mass of the conductive particles, and also contains 0.05% to 0.5% by mass of a clustering agent based on the content of the conductive particles, and 25% to 300% by mass of an alkoxysilane oligomer based on the content of the conductive particles. In the particle size distribution of the coating liquid measured using a dynamic light scattering particle size analyzer, the volume average particle size is 70 nm to 600 nm; based on volume, the particle size D is calculated when 16% of the particles are accumulated from the smaller particle size side. 16 Particle size D when accumulated to 84% 84 The difference (D) 84 -D 16 The wavelength range is 60nm to 800nm.

6. A substrate with a conductive coating, characterized in that, A film obtained from the coating liquid of claim 5 is disposed on the substrate.

Citation Information

Patent Citations

  • Manufacturing method of chain-shaped conductive fine particle, chain-shaped conductive fine particle, paint for transparent conductive coating formation, and base material with transparent conductive coating

    JP2006339113A

  • Coating composition, conductive film, and liquid crystal display panel

    JP2019157026A

  • Conductive composite, conductive film and conductive film manufacturing method

    CN106147198A

  • Electroconductive dispersion, electroconductive coating material and their production

    JP1997031238A